2015
DOI: 10.1158/0008-5472.can-15-0650
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Cells Respond Differentially to Modulation of TGFβ2 Signaling after Exposure to Chemotherapy or Hypoxia

Abstract: Intratumoral heterogeneity helps drive the selection for diverse therapy-resistant cell populations. In this study, we demonstrate the coexistence of two therapy-resistant populations with distinct properties that are reproducibly enriched under conditions that characterize tumor pathophysiology. Breast cancer cells that survived chemotherapy or hypoxia were enriched for cells expressing the major hyaluronic acid receptor CD44. However, only CD44 hi cells that survived chemotherapy exhibited cancer stem cell (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
1
6
1
Order By: Relevance
“…Although we did not observe signi cant changes in the expression of CD24 ( Fig. S2A), another CSC-speci c marker, previous studies have proven that CD44 expression is adequate for CSC population selection [15]. These data indicated that DOC treatment induced the enrichment of CD44 hi population which could be signi cantly inhibited by Fig.…”
Section: Decitabine Inhibits the Csc Enrichment Induced By Dab2ip Hypcontrasting
confidence: 48%
See 1 more Smart Citation
“…Although we did not observe signi cant changes in the expression of CD24 ( Fig. S2A), another CSC-speci c marker, previous studies have proven that CD44 expression is adequate for CSC population selection [15]. These data indicated that DOC treatment induced the enrichment of CD44 hi population which could be signi cantly inhibited by Fig.…”
Section: Decitabine Inhibits the Csc Enrichment Induced By Dab2ip Hypcontrasting
confidence: 48%
“…Several studies revealed that cells surviving after chemotherapy exhibited high CSC capacities (selfrenewal ability and CD44 expression) [9,15]. To analyze the changes of CSC population under DOC or DAC+DOC treatment, we labeled CSCs and dead cells with anti-CD44 antibodies and PI, respectively.…”
Section: Decitabine Inhibits the Csc Enrichment Induced By Dab2ip Hypmentioning
confidence: 99%
“…L1CAM, ANGPTL4, CA9, VEGFA, LDHA, P4HA1, LOX, LOXL2, LOXL4) are almost all significantly upregulated in both BRC12/CD184 lo and BRC13/CD49f lo cells (S3 Table). Hypoxia is often correlated with therapeutic resistance [43,44]. In accordance with this, gene expression signatures of drug resistance can also be found in those same populations (S8 Fig).…”
Section: Discussionsupporting
confidence: 72%
“…Cancer initiating cells (CICs), also referred to as cancer stem cells, are recognized as a significant problem in effectively managing breast cancer. CICs are known for their resistance to chemotherapy, ability to form non-adherent mammospheres in vitro, and high tumorigenicity in vivo [ 3 , 4 , 5 , 6 , 7 ]. Standard chemotherapies (e.g., taxanes) have been shown to enrich the population of CICs in TNBC [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%